Absorbable versus silk sutures for surgical treatment of trachomatous trichiasis in Ethiopia: a randomised controlled trial. - Saul N Rajak (Public Library of Science (PLoS), 2011)
Background Trachoma causes blindness through an anatomical abnormality called trichiasis (lashes touching the eye). Trichiasis can recur after corrective surgery. We tested the hypothesis that using absorbable sutures instead of silk sutures might reduce the risk of recurrent disease among patients with major trichiasis in a randomised trial. Methods and findings 1,300 individuals with major trichiasis from rural villages in the Amhara Region of Ethiopia were recruited and assigned (1:1) by computer-generated randomisation sequence to receive trichiasis surgery using either an absorbable suture (polyglactin-910) or silk sutures (removed at 7-10 days) in an otherwise identical surgical technique. Participants were examined every 6 months for 2 years by clinicians masked to allocation. The primary outcome measure was recurrent trichiasis (≥one lash touching the eye) at 1 year. There was no difference in prevalence of recurrent trichiasis at 1 year (114 [18.2%] in the absorbable suture group versus 120 [19.7%] in the silk suture group; odds ratio = 0.90, 95% CI 0.68-1.20). The two groups also did not differ in terms of corneal opacification, visual acuity, conjunctival inflammation, and surgical complications. Conclusions There was no evidence that use of absorbable polyglactin-910 sutures was associated with a lower prevalence of trichiasis recurrence at 1 year postsurgery than silk sutures. However, from a programmatic perspective, polyglactin-910 offers the major advantage that patients do not have to be seen soon after surgery for suture removal. The postoperative review after surgery using absorbable polyglactin-910 sutures can be delayed for 3-6 months, which might allow us to better determine whether a patient needs additional surgery. Trial registration ClinicalTrials.gov NCT00522860.